REFORMS IN THE FIELD OF EDUCATION IN THE EXAMPLE OF THE 11TH SCHOOL - Djuraboyeva Ravshankhan Tokhtasinovna (American Journals, 2023)
The essence of the law of the Republic of Uzbekistan dated June 21, 2022 "On measures to increase the quality of pedagogical education and further develop the activities of higher educational institutions training pedagogic personnel" in Andijan city 11th general education school case was considered and the practice of the law in a short period was analyzed.
Keywords: Right to education, Law